2021
DOI: 10.1186/s12879-021-06819-9
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic liver abscess in a COVID-19 patient: a case report

Abstract: Background Amoebiasis is a parasitic disease caused by Entamoeba histolytica, which affects people living in low- and middle-income countries and has intestinal and extraintestinal manifestations. To date, knowledge on coronavirus disease 2019 (COVID-19) coinfection with enteric parasites is limited, and E. histolytica coinfection has not been previously described. Here we present the case of a patient with COVID-19 who, during hospitalisation, presented a clinical picture consistent with an am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Conversely, a recent study14 found that co-infection with parasitic diseases appears to be associated with reduced severity in patient with COVID-19, suggesting that parasite-driven immunomodulatory responses may mute the hyperinflammation associated with severe COVID-19. Based on their pathophysiological similarities, co-infection with SARS-CoV-2 and E. histolytica might change the patient’s clinical course; however, larger studies are needed to fully understand the interaction between these pathogens.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Conversely, a recent study14 found that co-infection with parasitic diseases appears to be associated with reduced severity in patient with COVID-19, suggesting that parasite-driven immunomodulatory responses may mute the hyperinflammation associated with severe COVID-19. Based on their pathophysiological similarities, co-infection with SARS-CoV-2 and E. histolytica might change the patient’s clinical course; however, larger studies are needed to fully understand the interaction between these pathogens.…”
Section: Discussionmentioning
confidence: 92%
“…Maricuto et al 14 have hypothesised that elevated PGE2 levels are secondary to both direct stimulation of cyclo-oxygenase-2 (COX-2) by SARS-CoV-2 and a COX-2-like protein present in E. histolytica trophozoites, which might influence the clinical course; however, the available evidence remains insufficient to establish any correlation.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to liver abscess, COVID-19 and TB patients commonly experience gastrointestinal symptoms, night sweats, cough, and weight loss, all of which are associated with both liver abscess and TB. Notably, liver abscess has been reported in a COVID-19 patient [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a case reported of ALA copresenting with coronavirus disease 2019. Based on pathophysiological similarities, coinfection with both of these could affect the clinical course of the patient[ 18 ].…”
Section: Complicationsmentioning
confidence: 99%